Soap Production from Waste Cooking Oil: A Review - Ahadito, Bijak Riyandi; Afriani, Siti Rakhmi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
In the process of cooking, chemical reactions that happen to the vegetable oil render it unfit for consumption after multiple reusage, thus turning the oil into waste. Due to the abundance of such waste, it is important to have an easy way to turn waste cooking oil into another useful commodity. Production of soap is one of such method that could be widely applied by the public due to the easiness of its procedures and no involvement of hazardous chemical, in contrast to the production of biodiesel or biofuel which sometimes demands the use of unsafe materials or conditions. The objective of this publication is to provide information about the differences between unused and used cooking oil, to lay out the methods of soapmaking, to review the academic reports of soapmaking from waste cooking oil, and to summarize the challenges that are still unsolved in this topic.